Nicknames Conveying by the Senior High School Students - Sri Wulan Suci; Rachmawati Rachmawati; Melati Melati (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
The current research seeks the variety of nicknames producing by the students at State Senior High School 1 Model Muaro Jambi. In conducting the present research, the descriptive qualitative desinged is employed where in the data are gathered by mean of  observation, note-taking, and interview. The students’ nicknames are categorized into two types: (1) nicknames directly related to their formal full name and (2) nicknames are not related to their formal full name. Such nicknames are constructed by five rules (Liao, 2000), i.e, (R1) affectionate names (duplication of one syllable/ character), (R2) one character of the full name (prefix), (R3) homophonic wordplay (alliterate, rhymed character and an object/ term associated with it), (R7) describe the person, ability, figure, fondness, etc., opposite quality and (R8) given by relatives. The analysis also shows that most students’ nicknames which are constructed by (R3) homophonic wordplay.Nicknames among students are employed to show an intimacy among their members in which the construction of the nicknames as a result of their creation. Some of them proud with their nicknames and others do not feel comfort.